Character Education and the Architecture of Social Trust: Revisiting the Role of Schools in Building Civic Communities - Diah Iskamtini; Salman Alfarisi; Tamsik Udin; Asep Mulyana (PT. Student Rihlah Indonesia, 2026)
This article revisits the role of schools in shaping civic communities by emphasizing the importance of character education and the construction of social trust. Amid a growing crisis of public trust and increasing social fragmentation, schools are positioned not merely as knowledge-transmitting institutions but as vital social arenas where values such as honesty, responsibility, tolerance, and solidarity are systematically cultivated. Combining theoretical insights with empirical findings from various multicultural schools in Indonesia, the study highlights the need for a deliberate architecture of social trust supported by curriculum, school culture, and community engagement. The findings suggest that a comprehensive integration of character education can foster cohesive social networks and strengthen the foundations of civic communities. The article advocates for empowering teachers as moral change agents and developing educational policies that prioritize social trust as a core principle in nation-building.